Development and Application of a Malaysian Socio-Technical Disaster Model - Mat Said, Aini (2006)
Understanding of the development and causes of the disasters provides a tool for organizational and institutional diagnosis of vulnerability and risks. The hindsight gained from these negative events could be utilized by government and enterprises to design organizational structures that will help reduce the likelihood of disaster as the nation progresses. A multi strategy research was designed utilizing qualitative and quantitative approach to develop a socio-technical disaster model and a learning system for Malaysia. Using a grounded theory approach, six inquiry reports were used to identify the phases associated with the development of the socio-technical disasters and their underlying causes. Management of the inquiry into these disasters and the recommendations made by the tribunal of inquiry were also analyzed. Nvivo software program was utilized to model the latent errors attributed to the disasters. A survey was conducted among Malaysian Disaster experts who were selected using judgmental sampling in order to determine their views on disaster and disaster inquiry management. Data obtained from both qualitative and quantitative study was then transferred into a Visual Basic 6.0 computer program to form a learning and advice model.